Adherence to assigned dosing regimen and sustained virological response among chronic hepatitis C genotype 1 patients treated with boceprevir plus peginterferon alfa‐2b/ribavirin. Issue 1 (26th May 2013) - Gordon, S. C.; Yoshida, E. M.; Lawitz, E. J.; Bacon, B. R.; Sulkowski, M. S.; Davis, M.; Poordad, F.; Bronowicki, J.‐P.; Esteban, R.; Sniukiene, V.; Burroughs, M. H.; Deng, W.; et al.
Summary Background Adherence to therapeutic regimens affects the efficacy of peginterferon alfa (P) and ribavirin (R) therapy in patients with chronic hepatitis C virus genotype 1. Aim To determine if medication adherence impacts efficacy [sustained virological response (SVR)] with triple therapy that includes boceprevir (BOC) plus P/R. Methods Adherence was determined in two Phase 3 clinical studies with BOC: SPRINT‐2 (previously untreated patients) and RESPOND‐2 (patients who failed previous therapy with P/R). Adherence to the assigned duration of the dosing regimen and adherence to the three times a day (t.d.s.) dosing interval of 7–9 h for BOC were assessed by the recording of data from patients' dosing diaries and by the amount of study drug dispensed and returned. Results Most patients (63–71%) adhered to ≥80% of their assigned treatment duration and achieved SVR rates of 86–90%. In contrast, patients who adhered to <80% of their assigned treatment duration achieved SVR rates of 8–32% (P < 0.0001), particularly low in patients who failed previous therapy (SVR = 8–15%). Different rates of adherence (<60% to >80%) to the t.d.s. dosing interval (7–9 h) with BOC did not influence the SVR rates (SVR = 60–83%) with the exception of patients who failed previous treatment and adhered to <60% of the t.d.s. dosing interval with BOC (SVR = 48–50%; P = 0.005). Conclusions The achievement of an SVR is more dependent on adherence to the assigned duration of treatment than adherence to the t.d.s. dosing interval with boceprevir. Adherence to >60% of t.d.s. dosing with boceprevir is important in patients who failed previous therapy.